3D-printed cranial helmet therapy for the treatment of deformational plagiocephaly - Atallah, Huthaifa; Naeem, Rabee; Albeetar, Raghad; Qufabz, Titeana; AlFatafta, Mahmoud; Alshawabka, Amneh; Said, Anas S.; McGarry, Anthony; Derkács, Evelin; Varga, Dorottya; Molics, Bálint (Frontiers in Pediatrics, 2025)
IntroductionDeformational Plagiocephaly (DP) is the most common cranial deformity in infants. It may be treated using molding cranial helmet therapy (CHT) or active counter-positioning (ACP). Molding CHT has proven to be highly effective, especially in moderate to severe cases. Although many studies have explored this topic, few have investigated the use of 3D-printed CHT. This method may offer greater accuracy and convenience in measurement compared to traditional helmet types. Furthermore, no studies on this subject have been conducted in the Middle East.Study designA retrospective study design.MethodsElectronic medical records from the only medical center fitting infants with 3D-printed CHT were reviewed. Infants diagnosed with DP who were fitted with and completed treatment using 3D-printed CHT were included. Infants who received 3D-printed CHT for other cranial deformities were excluded. Descriptive statistics (mean ± SD) were used to present results related to Cranial Vault Asymmetry Index (CVAI) and participants' characteristics. A Linear Mixed Model was used to assess changes in CVAI over time, accounting for age, gender, and treatment duration. Model assumptions were tested, and findings were validated using a Wilcoxon signed-rank test.ResultsRecords of eleven infants diagnosed with DP were included, eight boys and three girls. A significant reduction in CVAI was reported in all cases. No significant correlation was found between CVAI improvement and gender, age, or treatment duration.ConclusionFollowing treatment with customized 3D-printed CHT, infants in the study demonstrated significant improvement in the CVAI. The helmets effectively guided cranial growth toward the flattened area, aiding in the correction of the deformity. Although 3D-printed CHT showed results comparable to traditional molding CHT, it offers potential advantages such as increased measurement accuracy through 3D scanning, easier monitoring of progress, and reduced cost and time associated with fabrication through 3D printing.